The effects of alcohol-related harms to others on self-perceived mental well-being in a Canadian sample - Lewis-Laietmark, C.; Wettlaufer, A.; Shield, K.; Giesbrecht, N.; April, N.; Asbridge, M.; Dell, C.; Rehm, J.; Stockwell, Tim (Birkhaeuser Science, 2016)
Objectives: To examine (1) the harms related to the drinking of others in five Canadian provinces, stratified by socio-demographic variables, and (2) the relationship between these harms and mental well-being. Methods: A telephone survey sampled 375 adults from British Columbia, Saskatchewan, Ontario, Quebec, and Nova Scotia. Harms related to the drinking of others were measured through 16 questions in the domains of psychological, physical, social, and financial harms. Self-perceived mental well-being was measured with his or her mental well-being. Results: In 2012, 40.1% of Canadian adults surveyed experienced harm in the previous year related to the drinking of another person. These harms were more frequent among people who had a higher education level, were widowed, separated, divorced or never married, and were employed. Psychological, physical, and financial harms related to the drinking of others were significantly correlated to a person’s mental well-being. Conclusions: Harms related to the drinking of others are prevalent in this Canadian survey. Furthermore, the psychological, physical, and financial harms related to the drinking of others negatively impact the mental well-being of the affected individuals.